Motivasi Menghafal Al-Qur'an Juz 30 Pada Peserta Didik Kelas VI Dalam Meningkatkan Belajar Baca Al-Qur’an Di Madrasah Ibtidaiah Yamra Merauke - 'Rudi Hartono (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2024)
This research aims to determine the process of memorization motivation, motivation factors, and achievement results for class VI students in increasing interest in learning to read the Al-Qur'an through motivation to memorize Al-Qur'an juz 30. This research is classified as a qualitative research type, a research approach that used: phenomenological. The data sources for this research are the Head of the Madrasah, the Head of the Al-Qur'an class coordinator, the Al-Qur'an class supervisor and the students. The data collection methods used were observation, interviews and documentation. Then, data processing and analysis techniques are carried out through three stages, namely: data reduction, data presentation, data verification and drawing conclusions. Research results: A. motivation process for memorizing Al-Qur'an Juz 30: 1) Students' self-awareness of learning, 2) Adjusting goals, 3) Learning to students' needs, 4) Giving a gentle touch, 5) Giving gifts, 6 ) Giving praise and respect, 7) Students knowing their learning achievements, 8) A healthy school environment, 9) Competent and humorous teachers. B. Factors that influence motivation to memorize the Qur'an: a) Internal factors, in the form of attitude, personality, education, experience and ideals. b) External factors, in the form of social and non-social environments. C. Student achievement results: 1) can memorize Juz 30 according to the target, 2) can read the Al-Qur'an well and correctly, and 3) master the science of recitation. Keywords: Al-Qurán, Motivation, Memorizing